Clusterization of Red Betel Leaves (Piper Crocatum) from Various Regions in Indonesia Based on Secondary Metabolite Fingerprint Analysis and Cytotoxicity Values - Eka Wahyu Purnama; Mega Safithri; Dimas Andrianto (Universitas Djuanda, 2023)
The quality of the ethanol extract of red betel leaves as a medicinal plant is determined by secondary metabolites, which are influenced by geographical conditions and the plant growing environment. This study aims to classify red betel from various regions in Indonesia based on secondary metabolite fingerprint analysis and cytotoxicity values. Observation of the diversity of secondary metabolites of the ethanol extract of red betel leaves from seven different regions (Banda Aceh, Bandung, Bogor, Malang, Samarinda, Kendari, Jayapura) was carried out using a metabolomics approach using liquid chromatography-mass spectroscopy (LC-MS/MS) and determining cytotoxicity value using the Brine Shrimp Lethality Test (BSLT) method. Secondary metabolite fingerprinting analysis using cluster analysis with dendrogram yielded 12 compounds with 3 sample groups based on their region of origin, namely group 1 (Banda Aceh, Samarinda, Jayapura); group 2 (Bandung, Kendari, Malang); group 3 (Bogor). Group 1 samples identified eight compounds that had the highest relative abundance values. Group 2 samples identified 3 compounds that have the highest relative abundance values. Group 3 samples had 1 compound with the highest relative abundance value. Each compound has a different retention time. The cytotoxicity value (LC50) of the ethanol extract of betel leaves was obtained from the Banda Aceh and Malang areas (2.64 µg/mL). The conclusions of this study based on the results of secondary metabolite fingerprinting analysis and cytotoxicity values ​​identified 12 compounds with three clusters of secondary metabolite diversity based on their region of origin, namely group 1 (Banda Aceh, Jayapura, Samarinda); group 2 (Bandung et al.); group 3 (Bogor).